Customized Barrier Membrane (Titanium Alloy, Poly Ether-Ether Ketone and Unsintered Hydroxyapatite/Poly-l-Lactide) for Guided Bone Regeneration - Shi, Yilin; Liu, Jin; Du, Mi; Zhang, Shengben; Liu, Yue; Yang, Hu; Shi, Ruiwen; Guo, Yuanyuan; Song, Feng; Zhao, Yajun; Lan, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Sufficient bone volume is indispensable in achieving both functional and aesthetic results in the fields of oral oncology, trauma and implantology. Currently, guided bone regeneration (GBR) is widely adopted to reconstruct alveolar ridge and repair bone defects with priority of low technical-sensitivity and considerable osteogenesis effect. However, traditional barrier membranes could not meet clinical needs of space-preserving ability or result in plenty of healing complications. To solve the problem, progress in digitalization and three-dimensional (3D) printing technology allow well space maintenance, precise predictability of bone graft and optimization of patient-specific strategies available by employing customized barrier membranes in GBR. The article reviews processes and advantages of three-dimensional computer-assisted surgery with GBR in maxillofacial reconstruction and alveolar bone augmentation, properties of materials used to fabricate customized bone regeneration sheets and promising bone regeneration potency in clinical application and up-to-date achievements. This review aims to present a reference of customized barrier membrane in clinical aspects and future applications.